2012
DOI: 10.1093/cid/cis777
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Incidence of Hepatocellular Carcinoma in HIV-Infected Patients in Spain

Abstract: HCC is an emerging complication of cirrhosis in HIV-infected patients. A sharp increase in its incidence has occurred in those also infected by HCV in the recent years. Unfortunately, HCC is frequently diagnosed at an advanced stage, and mortality continues to be very high, with no significant changes in recent years. Earlier diagnosis, which may allow potentially curative therapy, is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 33 publications
7
46
1
3
Order By: Relevance
“…Overall, the incidence of HCC is increasing, not only in the general population of patients with cirrhosis [11,12] , but particularly in some subgroups of patients, like those with human immunodeficiency virus (HIV) infection or thalassemia. In fact, in both HIV and thalassemia, a recent significant outcome improvement due to, respectively, iron chelating drugs in the latter and highly active antiretroviral therapy in the former, has allowed the appearance of the complication of the underlying hepatic disease [13][14][15][16][17][18] .…”
Section: Reviewmentioning
confidence: 99%
“…Overall, the incidence of HCC is increasing, not only in the general population of patients with cirrhosis [11,12] , but particularly in some subgroups of patients, like those with human immunodeficiency virus (HIV) infection or thalassemia. In fact, in both HIV and thalassemia, a recent significant outcome improvement due to, respectively, iron chelating drugs in the latter and highly active antiretroviral therapy in the former, has allowed the appearance of the complication of the underlying hepatic disease [13][14][15][16][17][18] .…”
Section: Reviewmentioning
confidence: 99%
“…Liver biopsy had been performed in 92 cases (69 %), a median time of 165 days (43-1043) before therapy. All the patients had fibrosis 4, and the median histological activity index (HAI) was 5.84 (4)(5)(6)(7)(8)(9)(10)(11)(12). The remaining 41 patients had a LSM before therapy confirming fibrosis 4.…”
Section: Resultsmentioning
confidence: 99%
“…HIV coinfection accelerates HCV progression [1], and time from diagnosis of cirrhosis to death is shorter in HIV-/HCV-coinfected patients [2]. Although the use of antiretroviral therapy can reduce the rate of liver complications [3], some experts suggested that the incidence of a liver event, such as hepatocellular carcinoma (HCC), could even increase in the future [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, los últimos datos disponibles de CHC en pacientes infectados por el VIH en España han confirmado que se está produciendo un aumento significativo del número de casos en los pacientes coinfectados. Así, en un registro retrospectivo de CHC en pacientes infectados por el VIH de 18 hospitales de Andalucía y la Comunidad Valenciana, de 82 CHC diagnosticados entre 1999 y 2010, 74 (90%) fueron diagnosticados a partir del 2004 22 . De esta forma, la incidencia de CHC en pacientes coinfectados pasó de 0,2 a 2,8 casos por 1.000 personas/año del 2000 al 2009 22 .…”
Section: Carcinoma Hepatocelularunclassified